Antimicrobial Activity of the Sumbawa Mare Milk - Hermawati D; Soekarto S T; Zakaria F R; Sudardjat S; Tjatur Rasa F.S (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
The research objectives where to verify the antimicrobial activity of mare milk from Sumbawa island and to further study the characteristics of the antimicrobial compound. The experiments were conducted involving 115 milk samples of Sumbawa mare and three different groups of control milk i.e. from 20 milk samples of working/ cart mares from Java, 2 samples of racing mares from Tangerang horse farm and 15 samples of dairy cows from Bogor. The results concluded that all milk samples of Sumbawa mares contained strong antimicrobial activity as tested to 9 species of bacteria. All control samples did not show antimicrobial activity, except milk samples from racing mares which showed low antibacterial activity. The racing mares were then indentified as crossbred between male Thoroughbred and female Sumbawa horse. This finding supports and suggests that the native Sumbawa horses have genetic potential to the antimicrobial activity in their milk produced. Polarity tests using 5 organic solvents of different polarity indicated that the antimicrobial activity compound was very polar but had lower polarity than water. The bioactive coumpound did not dissolve in non polar hexane but strongly dissolved in the polar methanol solvent. Key words : Mare milk, Sumbawa horses, antimicrobial activity, milk protein.